Uro under overflaten: Modernisme i Knut Hamsuns «Ringen sluttet» (1936) - Børset, Bodil (Nordlit, 2016)
This article examines Hamsun’s The Ring is Closed (1936) through the lens of modernity and modernism. A common notion has been that The Ring is Closed is an exception from the division between an early modernist phase and a later realist phase in Hamsun’s oeuvre. This article argues that Hamsun deals with modernity in a fundamentally different way in 1936 than he did in the 1890s. Today we should be able to see Abel Brodersen’s fatalism, cynicism, and lack of drive as an expression of 1930s modernism. What are the characteristics of such modernism? To which of his contemporary modernist characters can we compare Abel Brodersen? What literary techniques does Hamsun employ, and how can we characterize the language and the narrative structure? How does the modernist Hamsun in 1936 compare to Hamsun in 1890? These are some of the questions posed in this article.